FEMORAL TUNNEL FIXATION FOR MEDIAL PATELLOFEMORAL LIGAMENT RECONSTRUCTION IN THE GROWING PATIENT IS SAFE FOR FUTURE GROWTH. Issue 4 (28th April 2020) - Gross, Bruno; Sabatino, Meagan J.; Brenner, Madison; Wyatt, Charles W.; Wilson, Philip; Ellis, Henry
Background: Medial patellofemoral ligament (MPFL) reconstruction has been shown to be a successful treatment for patients with recurrent patellar instability and is increasingly used to treat skeletally immature patients. Purpose: The purpose of this study is to compare radiographic parameters prior to and following an MPFL reconstruction with femoral tunnel fixation in the skeletally immature patient to investigate potential effects on the physis and future growth. Methods: Skeletally immature patients undergoing isolated MPFL reconstruction were retrospectively reviewed. Fixation of proximal MPFL was performed as a femoral socket using Schottle's point with the entry approximately 5 mm distal to the physis (Figure 1). Patients with open growth plates and 1-year post-operative standing alignments were included. Radiographic measures of patellar tilt, patellar height, patellar subluxation, and trochlear dysplasia were compared pre-operatively and post-operatively on the operative limb. Pre- and post-operative coronal alignment and limb length measurements were compared between the operative and non-operative limbs. Results: Nineteen skeletally immature patients with an average age of 11.6 years (range 5-15) underwent isolated MPFL reconstruction. The average follow-up time was 24 months. No significant differences were found between the change in femur (0.49 mm, p=0.526) or total limb length (1.08 mm, p=0.241) when comparing the operative to the non-operative limb, with an average of 47 mm of growth in the operative limb seen during the time period. There was no significant difference in the change in LDFA between operative and non-operative limb as well as symmetric changes noted in the mechanical axis. The change in patellar tilt on the operative limb was found to be significant (12.78°, p=0.030), and the change in patellar height by Caton-Deschamps approached significance (0.08mm, p= 0.077). No significant difference was found with trochlear dysplasia measures. Conclusion: The present study suggests MPFL reconstruction with femoral tunnel fixation is safe and does not result in growth disturbance in skeletally immature patients. : Figure 1. Fluoroscopic images of the femoral placement of the bone tunnel for the medial patellofemoral ligament reconstruction in a 13 year old male utilizing Schottle point and remaining distal to the physis. (A) Lateral view of the knee (B) Notch view of the knee in order to confirm position of the guide pin distal to the physis posteriorly.